Food and nutrition security implications of crop diversification in Malawi’s farm households - Mazunda, John; Kankwamba, Henry; Pauw, Karl (International Food Policy Research Institute, 2018)
This chapter provides selected details from a study of the links between crop production diversity and dietary diversity among Malawian households. We use data from Malawi’s Third Integrated Household Survey (2010–2011) to construct a food group–based, household-level dietary diversity score. To sharpen our “nutrition lens,” we also construct indicators for household-level access to micronutrients. Results indicate significant and positive associations between food crop production diversification and both types of indicators. The strongest associations are for households’ micronutrient access. Production diversification is associated with a 35 percent increase in access to iron, a 47 percent increase in access to vitamin A, a 45 percent increase in access to folate, and a 35 percent increase in access to zinc. As deficiencies in these micronutrients continue to present a public health challenge in Malawi, these findings support the hypothesis that crop production diversification is a viable option to increase nutrition sensitivity in agriculture.